NOMAC-E2 compares to LNG combined oral contraceptives in women over forty: real-world PRO-E2 study. (14th December 2023) - von Stockum, Sophia; Becker, Kerstin; Bauerfeind, Anja; Franke, Christian; Fruzzetti, Franca; Calaf, Joaquim; Keck, Christoph; Heinemann, Klaas
Abstract: Objective: To investigate safety and effectiveness of NOMAC-E2 and levonorgestrel-containing COCs (COCLNG ) in users over 40. Methods: In this large, observational study, new users 1 of NOMAC-E2 and COCLNG were recruited in Europe, Australia, and Latin America and followed-up via questionnaires. Incidence of venous thromboembolism (VTE) was expressed as incidence rate (IR; events/10 4 women-years [WY]). Unintended pregnancy was expressed by the Pearl Index (PI; contraceptive failures/100 WY). Mood and weight changes were defined as mean changes in mood score and percentage of body weight. Results: Overall, 7, 762 NOMAC-E2 and 6, 059 COCLNG users over 40 were followed-up. NOMAC-E2 showed no increased VTE risk compared to COCLNG ; confirmed events: 5 NOMAC-E2 (IR 5.9; 95% CI, 1.9–13.7) vs 4 COCLNG (IR 5.9; 95% CI, 1.6–15.1). Unintended pregnancy did not differ substantially between cohorts; confirmed events: 4 NOMAC-E2 (PI 0.05; 95% CI, 0.01–0.13) vs 5 COCLNG (PI 0.08; 95% CI, 0.03–0.18). No differential effect on mood and weight was observed between cohorts. Conclusions: NOMAC-E2 can be considered a valid alternative to COCLNG in perimenopausal women.